Um Método Para Avaliar o Pensamento Espacial em Mapas Sociais Web - Silva Neto, André Avelino da; Mota, Marcelle Pereira (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Spatial thinking can be understood as the ability to interpret cartographic data and make decisions based on them. In the context of social cartographic data, this ability can be decisive for the user to understand social issues and propose actions for change. The present study aims to facilitate public access to this data and encourage proposals for social change. To this end, a method will be proposed for evaluating spatial thinking in the context of web map applications with social data. The idea is that this method supports new discoveries to favor and stimulate spatial thinking in these applications, especially in the area of Human-Computer Interaction (HCI).